Pendidikan Karakter Perspektif Al-Qur’an - Slamet Yahya (INSANIA : Jurnal Pemikiran Alternatif Kependidikan, 2013)
Abstract: Character education is now indeed become a major issue of education in Indonesia today. In addition to being part of the process of formation of the child character, character education is also expected to become a major foundation in the form of qualified personal and responsible generation. Lately more and more people realize the importance of character education or in Islam is called the noble character education. In addition to being part of the process of formation of the child character, character education is also expected to become a major foundation in the form of qualified personal and responsible generation. Character education has been applied in various educational institutions as a form of policy to realize the Ministry of National Development National Movement National Character. In the implementation of character education, educational institutions have to equip teachers to integrate character education values with a comprehensive variety of methods. In this paper, the author will try to discuss about perespektif character education in the Koran. Keywords : education, character, the Koran.